Settlement of Medical Crimes by the Medical Committee and Medical Audit - Ningsih, Desy Kartika; Ravena, Dey; Rahim, Agus Hadian (NAJAHA, 2023)
In the context of a medical audit, the medical committee functions to prevent possible negligence in specific medical procedures. This function is generally performed when a case is considered difficult, an unnatural death or other exciting cases are found. This study aims to explain the role of medical committees and medical audits and the part of medical audits in resolving medical crimes. The method used in this study is a normative juridical method with a statutory and conceptual approach. This study shows that the medical committee is tasked with monitoring and evaluating the quality of medical services by implementing medical audits. Meanwhile, the role of medical audit in resolving medical crimes is as a guide to ensure that every action, procedure, mechanism and decision taken in medical treatment is by established standards and quality. In conclusion, the findings highlight the critical role of medical audits in ensuring the quality of medical services, preventing medical crimes, promoting accountability, and supporting due process. Emphasizing the importance of medical audits can lead to better patient care, increased trust in the healthcare system, and continuous improvement in the medical field.